Community-based animal genetic resources conservation: Lessons and practical applications - Alemayehu, N.; Gebru, G.; Drucker, Adam G. (Ethiopian Society of Animal Production, 2004)
This paper describes the importance of the community-based management of animal genetic resources and, based on existing participatory community-level projects, identifies crucial elements for the successful implementation of such programmes. These include: increased public awareness, promoting the use of participatory skills, improved natural resource management, increased consideration of gender issues. Improved indigenous breed commercialisation and marketing, and an appropriate enabling environment (i.e. policies and institutions). A methodology for implementing such programmes in Ethiopia is then presented together with some of the difficulties that need to be overcome in the establishment of participatory programmes, as well as the specific interventions that are required at a number of different levels.